3(9x+7)=27x-1

Simple and best practice solution for 3(9x+7)=27x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(9x+7)=27x-1 equation:


Simplifying
3(9x + 7) = 27x + -1

Reorder the terms:
3(7 + 9x) = 27x + -1
(7 * 3 + 9x * 3) = 27x + -1
(21 + 27x) = 27x + -1

Reorder the terms:
21 + 27x = -1 + 27x

Add '-27x' to each side of the equation.
21 + 27x + -27x = -1 + 27x + -27x

Combine like terms: 27x + -27x = 0
21 + 0 = -1 + 27x + -27x
21 = -1 + 27x + -27x

Combine like terms: 27x + -27x = 0
21 = -1 + 0
21 = -1

Solving
21 = -1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5(3-2x)=10(4-2x)-85 | | 4(x-10)=5x-45 | | 2x-5x-2=-3+4x-43 | | y=-1+-0.1666666667x | | IV=ir | | a^4-1698a-2704=0 | | 88-6x=-10x+85 | | -46-8x=5(-7x+7) | | 3=5-2 | | 75+10=15h | | 2(1.5)-3y=2 | | 4u-6=-2 | | p-0.30p=25.20 | | -20=4w | | 8x+6x-20=60-6x | | 7x+4q=8+3q | | 2(y)+8=8 | | y=x^3-6x^2-36x+15 | | 8=0.25(-m-1) | | 3(-3+2x)=9 | | 3m+n=35 | | 3(x+1)+2(2x-6)=33 | | 3x^3+2x^2+-41x+-66=0 | | 8a-48=-6(-6-6a) | | 6(2-3x)=4(5x+7) | | 2(5*555*5)-56= | | 5y+60-9=12+8y-72 | | 200*50+20= | | 9m+5=9m+6 | | m=n-7 | | -34m=12 | | 2x-9y=-3 |

Equations solver categories